Wetlands for food - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The vast 200 million hectares of wetlands in sub-Saharan Africa represent a great potential for food production if effectively utilized, says a report from the International Institute of Tropical Agriculture (IITA) in Ibadan, Nigeria. According to...